2021
DOI: 10.1080/00076791.2021.1896706
|View full text |Cite
|
Sign up to set email alerts
|

Feminist frustrations: The enduring neglect of a women’s business history and the opportunity for radical change

Abstract: In response to a special call of 'bringing gender and feminism from the periphery to the centre of business history' , the authors undertake an in-depth appraisal of Business History's own record, as a key signifier of the field. The scope includes articles and reviews published between 2000 and 2020 and find 17 articles out of 918 (1.85%) and 99 reviews out of 2,217 (4.46%), with a downward trend from 2010 to 2020. To start, the authors engage with a critical question as to the definition of the field itself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Feminist historiography is an act of resistance against masculine-centric narratives that dominate the past. Feminists engaged in history engage in various forms of resistance from uncovering silences (Haran, 2011) to offering alternative accounts (Wallach Scott and Tilly, 1975), to addressing the neglect of female actors (Mills and Williams, 2021) and more. By untangling grand, taken-for-granted narratives, we can overcover a more nuanced record of lived experience, history and culture (Ruel and Hammel, 2020; de Vaujany et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Feminist historiography is an act of resistance against masculine-centric narratives that dominate the past. Feminists engaged in history engage in various forms of resistance from uncovering silences (Haran, 2011) to offering alternative accounts (Wallach Scott and Tilly, 1975), to addressing the neglect of female actors (Mills and Williams, 2021) and more. By untangling grand, taken-for-granted narratives, we can overcover a more nuanced record of lived experience, history and culture (Ruel and Hammel, 2020; de Vaujany et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ficto-feminism is an activist method for two reasons. First, it is a method which confronts and protests against current taken-for-granted strategies of reconciling the historical record by simply adding in missing pieces (for example, see Graham, 1996; Mills and Williams, 2021). Instead, I wish to offer an account which constructs a rich portrayal of a neglected historical actor and her contributions, to management theory and practice.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Mills and Novicevic (2020) reviewed the scholarly output of three top MH journals between 2006 and 2018 and found that only 1.8% had anything to say about gender, feminism or women's history ( Management and Organizational History, Business History and Journal of Management History ). A forthcoming article by Mills and Williams (2021) reveals that the journal Business History (one of the field's most prominent journals) indicates that the trend to engage with women as historical actors or gender and feminism has decreased over the last 10 years. Granted, MH journals are not the only place where scholarship should engage with gender, feminism and history, but it speaks to systemic exclusions in MOS/MH, and it makes the call by the Qualitative Research Journal for activist methodologies inside and outside of the academy all the timelier and more important.…”
Section: Introductionmentioning
confidence: 99%